SEALING PERFORMANCE ANALYSIS AND STRUCTURAL OPTIMIZATION DESIGN OF NEW BEAM SEAL - YAN GuoHua; REN XinJiang; LIU Yong (Jixie qiangdu)
In order to improve the sealing performance of the beam seal, the structural parameters of the beam seal were used as design variables, and the optimization design was carried out. Firstly, a finite element model of the beam seal with elliptical are groove was established. Secondly, taking the maximum contact pressure of the sealing contact surface as a quantitative indicator of sealing performance, the sensitivity analysis of five structural parameters that affect the sealing performance of the beam seal was carried out, and the structural parameters with significant effects were selected to establish a second-order response surface model. Finally, the genetic algorithm was used to solve the multi-objective optimization of thel response surface model, and the effectiveness of the optimization results was verified by the finite element numerical simulation. The results show that the three parameters of the ellipse semi-major axis, the elliptic semi-minor axis and the nominal width of thefirst seal have a more significant impact on the sealing performance of the beam seal. When the three values are taken as 1. 051 mm, 0. 540 mm and 0. 060 mm respectively, the sealing performance of the beam seal can be effectively improved.